Product Country Of Origin And Its Impacts On The Customer Decision Making Process: A Study Over Malaysian Citizens In Automobile Industry - Moussavi, Seyed Ali (2009)
This study targets the citizens of Malaysia and their perceptions about Automobile industry. For this study, three different Country of Origins which are, Made in Malaysia, Made in Japan and Japanese brand assembled in Malaysia are considered and since Malaysian citizens are from three dominant ethnicities namely, Malay, Chinese and Indian, therefore this study is conducted based on a cross cultural concept to provide an idea about the perception of each ethnicity and a comparison between them. Moreover the level of ethnocentrism is measured for each ethnicity to investigate and compare its effect on the decision making of customers.